TITHE WEBSITE MAKING AND USING HTML AND VBSCRIPT CALCULATION - Herman Indra Sakti; Ir. Don Elsyafitra (Jurnal Sistem Informasi, 2002)
Islam is a religion that has a universal or comprehensive nature. Islam thus bettermanage all aspects of economic life, social, cultural, political. One of the importantaspects of life forms the social aspect. And regulate with the Islamic tithe.Tithe is an important aspect of societal life. Inside Islam to know the value of charity,issued a person must use the calculation of tithe or should know the science itself.In line with the global information age where information can be obtained quicklyand completely sophisticated information is needed fast, accurate and practical aboutthe charity, that is by computerize tithe calculation and can be accessed using theInternet. Makes it easier for Muslims to get information and know the amount of tithemust be spent. Program This website making programs using HTML and VBScript.